The complete mitochondrial genome of the marine polychaete: Perinereis aibuhitensis (Phyllodocida, Nereididae). (2nd November 2015) - Kim, Hana; Jung, Gila; Lee, Yu-Cheol; Pae, Se-Jin; Kim, Choong-Gon; Lee, Youn-Ho
Abstract: We determined the complete mitochondrial genome sequence of the marine polychaete Perinereis aibuhitensis (Grube, 1878) (Phyllodocida, Nereididae), a dominant species in the mudflat of the West Pacific and Indian Ocean. The complete genome of P. aibuhitensis is 15, 852 bp in size including 13 protein coding genes (PCGs), 2 rRNA and 22 tRNA with the same gene order and structure as those of other Nereididae species. The nucleotide composition is 29.5% A, 21.2% C, 14.1% G, 35.2% T, showing a high content of A + T with G being used least in the third codon position (6.7%). All PCGs use ATG as the start codon while for the stop codon COI and ND1 use incomplete codon of T. The mitogenome sequence of P. aibuhitensis is second to that of P. nuntia known in the genus Perinereis, which will provide useful information for understanding evolutionary history of the genus Perinereis within the family Nereididae.